Potenciali sodelovanja knjižnic, muzejev in arhivov kot dediščinskih ustanov - Zorko, Teja (Knjižnica, 2022)
Purpose: Cultural heritage is seen to be in the intersection of heritage institutions, libraries, archives and museums. The theme of linking these institutions has long been a hot topic abroad, driven by various social changes, as well as by administrative and financial trends and cultural policy decisions. This topic has not yet been explored in Slovenia, so the main aim of this paper is to present the views of those responsible, to identify the current situation, the perceived needs and the recommendations, which could be made. Methodology/approach: A study was carried out from January to April 2022, in which the management of all three types of institutions were invited to take part in a semistructured indepth interview. Theoretically, the survey was positioned within a broader sociological model of the public sphere, that allows for understanding change or resistance to change in libraries, archives and museums as public spaces, and more narrowly, within the theory of organisational learning, especially in terms of learning between organisations in the manner of absorptive capacity and systems thinking, and equipped with a typology of levels of collaboration on the scale of a collaborative continuum. Of the 26 invited, 19 persons took part in the survey. Results: The interviewees were mostly positive about their own institution’s collaboration with the other two disciplines and highlighted the positive effects of such collaborations in the future. The survey showed that cooperation between libraries, archives and museums is relatively superficial and remains at the beginning stages of the cooperation continuum. Through the interviews, certain systemic and concrete barriers and untapped opportunities were highlighted. Research limitations: The survey represents an initial impulse into a relatively new research topic, which consequently raises a number of new questions, at least in the field of staff training, digital content and materials processing, which are not addressed in the present study. Originality/practical implications: The possibility of collaboration between libraries, archives and museums is still relatively unknown in Slovenia, and there is no government policy support in the form of possible incentives for e.g. networking projects, which would enable initiatives for indepth heritage activities at the level of shared libraries, archives and museums to obtain additional funding or offer other appropriate forms of support.
Keywords: archives; arhivi; cultural heritage; knjižnice; kulturna dediščina; libraries; museums; muzeji; organisational learning; organizacijsko učenje; Slovenija